QUIZIZZ AS AN ALTERNATIVE GAME FOR TEACHING NARRATIVE TEXTS ON THE TENTH GRADE STUDENTS OF MAN 2 PALEMBANG - Marleni Marleni; Vira Zalika (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2021)
Abstrak Tujuanidari penelitiandini untuk mengetahuiz“Apakah ada perbedaan yang signifikan dalam pembelajaran teks naratif terhadap siswa kelas X MAN 2 Palembang antara yang diajar dengan menggunakan Quizizz dan yang tidak menggunakan Quizizz?”. Penelitian ini menggunakan desain eksperimen semu. Sampelipada penelitian ini 62 siswa yang diambil dengan menggunakan cluster random sampling. Dataidianalisis dengan menggunakan uji-t. Nilai siswa pada post-test kelompok eksperimen secara signifikan lebih tinggi daripada nilaiosiswa pada post-test kelompok kontrol. Artinya t yang diperoleh lebih besar dari t tabel 1,670. Maka, hipotesis alternatif (Ha) diterima dan hipotesis nol (Ho) ditolak. Dapat disimpulkan bahwa, ada perbedaan yang signifikan dalam pembelajaran teksinaratifipada siswa kelas X MAN 2 Palembang antara yang diajar dengan menggunakan Quizizz dan tidak menggunakan Quizizz.. Kata kunci: Quizizz, game alternatif, Mengajar, Membaca, Teks Naratif Abstract The main problem of this study was “Is there any significant difference in learning narrative texts to the tenth grade students of MAN 2 Palembang between those who are taught by using Quizizz and those who are not?”. This study appliedia Quasi-experimental design. Theisample of this study was 62 students taken by using cluster random sampling. The data was analyzed by using t-test. The students’ scores in post-test of experimentalogroup were significantly higher than the students’ scores in post-test of control group. It means that t-obtained was higher than t-table 1.670 as critical value. Consequently, the alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected. It could be concluded that, there is any significant difference inilearning narrative texts toithe tenth grade students of MAN 2 Palembang between those who are taught by using Quizizz as an alternative game and those who are not. Keywords: Quizizz, Alternative game, Teaching, Reading, Narrative Texts